Legal Model of the Protection of Self-Employment – Introduction to the Discussion - Duraj, Tomasz (Acta Universitatis Lodziensis. Folia Iuridica, 2022)
The main objective of the foregoing study is to introduce the reader to the issues of legal protection of self-employment in Poland, which was the subject of the IV National Scientiﬁc Conference from the series “Atypical employment relations” organized in Lodz on December 8–9, 2021 by the Center for Atypical Employment Relations at the Faculty of Law and Administration University of Lodz. This event was part of the promotion of a scientiﬁc grant carried out under the direction of Prof. Tomasz Duraj as part of an international project ﬁnanced by the National Science Centre entitled: “In search of a legal model of self-employment in Poland. Comparative legal analysis”. The author presents his own reﬂections de lege lata and de lege ferenda on the optimal model of legal protection of self-employment in our country.